"They're thinking, well it's not as bad, I probably won't get addicted to that. But it's still got the nicotine in it, so…": Maturity, Control, and Socializing: Negotiating Identities in Relation to Smoking and Vaping—A Qualitative Study of Young Adults in Scotland. Issue 1 (4th November 2017) - Lucherini, Mark; Rooke, Catriona; Amos, Amanda
Abstract: Objective: To explore the understandings of and engagement with e-cigarettes, of young adults from disadvantaged backgrounds, and how these may have an impact on existing smoking identities. Methods: Twenty-two small group and 11 individual qualitative interviews were conducted in Central Scotland with 72 16–24 year olds between September 2015 and April 2016. Participants were mostly smokers and ex-smokers from socioeconomically disadvantaged backgrounds. Results: Although most participants had tried e-cigarettes, they generally held ambivalent views about e-cigarettes and vaping. Two overarching themes were identified which helped in understanding this. Firstly, e-cigarettes were understood by the participants in relation to their existing smoking identities. Vaping was viewed as less controllable and more addictive than smoking, which did not fit with their self-identity as controlled smokers. Secondly, they felt that vaping could not replace the social and cultural importance that smoking had in their lives. Conclusion: This study suggests that though young adults from disadvantaged areas are trying e-cigarettes for various reasons, vaping is rarely sustained. Through their own experiences of vaping and their observations of others vaping, the participants perceive the behavior as endangering an existing acceptable and controlled smoking identity. Additionally, e-cigarettes were considered to be a jarring presence in existing social situations where smoking was valued. This study, therefore, provides insights into how young adults may be rationalizing their continued smoking in the face of potentially less harmful alternatives. Implications: As new and novel nicotine delivery devices, and due to their similarity to smoking, e-cigarettes have the potential to help smokers in their quit attempts. However, the findings from this study raise questions about whether e-cigarettes are regarded as having this potential by young adult smokers from disadvantaged socioeconomic environments where smoking is more commonplace and acceptable.